Development of injectable demineralized-bone and hydroxyapatite-nanoparticle composites as a bone graft material for effective healing of rat calvarial defect - Lee, Jung soo; Kim, Young Sik; Lee, Keun soo; Kang, Young Mo; Lim, Yong Woo; Jang, Ju Woong; Kim, Moon Suk (Materials Today Communications, 2023)
Demineralized bone matrix (DBM) possesses adequate osteoinductive and osteoconductive capabilities but can be rapidly absorbed prior to bone formation. Therefore, our study sought to design and optimize an injectable DBM formulation incorporating osteoconductive hydroxyapatite nanoparticles (HNP) to regulate the resorption rate of injectable DBM/HNP (DH) and promote bone regeneration at the bone defect site. Injectable bone graft materials were prepared by blending varying concentrations of carboxymethyl cellulose (CMC, 5–7 wt%) with different DH ratios. The complex viscosity of the injectable bone graft materials increased as both DBM and CMC concentrations in the mixing ratio increased. Physical property evaluations demonstrated that DH55 with a 5–7 wt% CMC concentration exhibited favorable handling characteristics, including injectability, shape retention, aggregation strength, and a high degree of adhesion between composites. Additional extrusion measurements revealed the extrusion force increased with higher CMC concentrations. Based on these results, DH55_5%-CMC (DH55_5-CMC) was determined as the final injectable formulation. Afterward, bone regeneration with DH55_5-CMC was compared to DBM_5-CMC as the control group using a rat calvarial defect model for 2 and 8 weeks. Micro-CT, H&E, and Masson's trichrome staining confirmed that DH55_5-CMC exhibited a higher extent of new bone formation compared to DBM_5-CMC. In summary, we successfully developed an injectable formulation with an optimized composition of DBM and HNP, featuring excellent physical handling properties and injectability. Furthermore, our findings confirmed that this injectable formulation has a profound impact on bone healing within the defect area.
Keywords: Bone formation; Bone graft; Bone graft materials; Calvarial defects; Demineralized bone matrix; Hydroxyapatite nanoparticles; Injectability; Injectable bone graft; Injectables; Osteoconductive; Demineralized bone matrix; Hydroxyapatite-nanoparticles; Injectability; Injectable bone graft